Reflux Complaints, Symptom Score and the Use of Medication in Patients with Reflux Esophagitis: Results of a Long-Term Follow-Up Study - Ruud JLF Loffeld (Canadian Journal of Gastroenterology)
Reflux esophagitis requires maintenance treatment. A cross-sectional descriptive study was done to assess the use of medication and prevalence of complaints in patients with esophagitis more than 4.5 years after diagnosis. All patients diagnosed with reflux esophagitis in 1995 received a questionnaire on reflux complaints and use of medication. A symptom score was assessed. Esophagitis was diagnosed in 173 patients; the questionnaire was sent to 130 patients, of whom 95 (74%) responded. Four groups of responders were identified: patients in clinical remission with (group 1, n=18) or without (group 2, n=20) maintenance therapy, and patients suffering from reflux complaints with (group 3, n=48) or without (group 4, n=9) medication. There was no statistically significant difference with respect to initial severity of esophagitis. Seventeen patients (94%) from group 1 and 32 patients (67%) from group 3 used medication on a daily basis (P=0.04). The mean symptom score ± SD, on a scale ranging from 0 to 80, was 7.8±5.3 in group 3 patients and 8.6±8.6 in group 4 patients (not significant). Patients in group 3 had a higher prevalence of retrosternal pain and nocturnal heartburn. It is concluded that most patients still use acid suppressive therapy more than 4.5 years after diagnosis. Only a small number are in clinical remission, although the symptom score is rather low.